Avaliação do ciclo de vida do glicerol oriundo da produção de biodiesel e seus processos de purificação - Silva, Wagner Menezes da (2012)
The Crude Glycerin, by-product of biodiesel manufacturing, became a problem for producers due to its low value of commercialization; besides, it does not have a real application on the industrial sector because of its high level of NaCl (~7%). These technical difficulties impede its absorption by the industry. On this paper we use the life cycle assessment methodology to evaluate the environmental performance of two processes of purification of Crude Glycerin, the distillation process and the viacetal process which is being developed by Petrobras. The system boundaries are assessed from cradle to gate, that is, we evaluate the glycerin from soybean cultivation to biodiesel production, oil extraction, transesterification and purification. The results on Greenhouse Gas point to the agricultural phase as the critical step in the life cycle of glycerol, representing 49% of 4167 kg CO2-Eqv per ton of Glycerol purified by distillation process while the purification process represents only 10% of this category of impact.